2003
DOI: 10.1259/bjr/66835905
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary complications following bone marrow transplantation

Abstract: Pulmonary complications account for significant morbidity and mortality in patients following bone marrow transplants (BMT). They are distinct from other immunosuppressed patients in that there is a predictable course of immunosuppresion and therefore of likely pulmonary complications. This is important when interpreting abnormal radiology as the predictable time course will enable narrowing the differential diagnoses to certain pulmonary complications that characteristically occur at a particular time followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
1
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 39 publications
1
64
1
9
Order By: Relevance
“…13,14,21,22 As for radiological tools, standard X-ray is the first line approach, even if it is not diagnostic in the majority of cases: hematologic patients typically have a decreased inflammatory response and clinical features, although variable and usually non-specific, may not manifest before the infection is far advanced. Thorax CT-scan, and particularly high resolution CTscan (HRCT-scan), offer a better approach: different studies showed a sensitivity and specificity of nearly 23 HRCT-scan can give us more information about type, number, localization of lesions, and their morphological characteristics. It can demonstrate the presence of the halo sign, a typical precocious lesion, or the presence of the air crescent sign, which usually becomes more prevalent later in the course of the disease.…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…13,14,21,22 As for radiological tools, standard X-ray is the first line approach, even if it is not diagnostic in the majority of cases: hematologic patients typically have a decreased inflammatory response and clinical features, although variable and usually non-specific, may not manifest before the infection is far advanced. Thorax CT-scan, and particularly high resolution CTscan (HRCT-scan), offer a better approach: different studies showed a sensitivity and specificity of nearly 23 HRCT-scan can give us more information about type, number, localization of lesions, and their morphological characteristics. It can demonstrate the presence of the halo sign, a typical precocious lesion, or the presence of the air crescent sign, which usually becomes more prevalent later in the course of the disease.…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…[1][2][3] Fungal infections are a frequent cause of pneumonia after HSCT with a reported incidence of up to 70%. 4 Effective prophylaxis to bacterial and viral pathogens results in increased frequency of invasive fungal infections (IFIs), which are the leading cause of infectious morbidity and mortality. Although fluconazole prophylaxis has reduced the incidence of infections caused by susceptible microorganisms, it resulted in a subsequent increase in the resistant species.…”
Section: Introductionmentioning
confidence: 99%
“…2 Table 2 lists the infectious causes of DAH. [9][10][11][12][13][14][15][16][17][18][19][20] It is important that clinicians remember that DAH can disguise itself in areas of infection as well as infarction. 2 As reflected in our case series, it seems reasonable to consider empirical antibiotic coverage while establishing a diagnosis.…”
Section: Differential Diagnosismentioning
confidence: 99%